Viewpoints: Dual-blocking antibody against VEGF-A and angiopoietin-2 for treating vascular diseases of the eye: forum - Koh, Gou Young; Augustin, Hellmut; Campochiaro, Peter (Trends in molecular medicine, 2022)
Faricimab, a bispecific antibody that targets the endothelial cell growth factors vascular endothelial growth factor-A (VEGF-A) and angiopoietin-2 (Angpt2), was recently approved for treating neovascular age-related macular degeneration and diabetic macular edema. Here, Koh and Augustin review how mechanistic studies have translated into therapies, while Campochiaro evaluates their impact and value for clinical practice.
Online verfügbar: 5 April 2022, Artikelversion: 28 April 2022
Gesehen am 26.02.2024